Answer: " r = a + b - s " .
_____________________________________________________
Step-by-step explanation:
_____________________________________________________
Given:
a + b = s + r ; Solve for: "r" ; that is; rewrite the equation in terms of: " r " .
_____________________________________________________
Subtract "s" from each side of the equation;
to isolate "r" on one side of the equation:
_____________________________________________________
→ a + b - s = s + r - s ;
→ to get:
→ a + b - s = r ;
____________________________________________________
↔ " r = a + b - s " .
____________________________________________________
→ which is the answer.
____________________________________________________
Hope this helps!
Best wishes to you!
____________________________________________________